A novel digital multi-mode control strategy with PSM for primary-side flyback converter. Issue 5 (4th May 2017) - Xu, Shen; Ni, Dandan; Lu, Shengli; Sun, Weifeng
ABSTRACT: This article described a novel digital multi-mode control strategy for primary-side controlled flyback converter to improve the efficiency within full-load range. The working modes of different load ranges were chosen according to the main power losses analysis and other constraint. Especially, a novel pulse skip mode control method which could reduce the number of actual switching cycles was proposed to improve the light load efficiency. A prototype with field-programmable gate array control has been made to verify the proposed digital multi-mode control strategy.